PENGARUH KONFLIK INTERPERSONAL DAN BEBAN KERJA TERHADAP STRES KERJA PADA PEGAWAI DI DINAS PERHUBUNGAN PROVINSI BALI - Agastya, Putu Yogi; Satrya, IGB Honor (E-Jurnal Manajemen, 2018)
This study aims to determine the Influence of Interpersonal Conflict and the Severe Expenses Against Job Stress on the employees at the Transportation Department of Bali Province. Interpersonal conflicts need to be considered to eliminate differences of opinion between individuals and other individuals. This research was conducted on all employees in Bali Transportation Department. The sample is 94 employees. The data was collected by distributing questionnaires using a 5-point likert scale to measure 15 statement items. The analysis technique used is Regression analysis. The results of this study indicate that Interpersonal Conflicts have a positive and significant effect on Work Stress and Workload has a positive and significant effect on Work Stress in Bali Provincial Transportation Department. Company managers must maintain and always pay attention to how much Job Stress is felt by employees. It aims to create employees who have important role attitudes in order to support the achievement of good performance in accordance with the objectives of relevant agencies in Bali Provincial Transportation Department.   Keywords: Interpersonal Conflict and Workload, Working Stress.